Vortex-induced vibration characteristics of two open girders: A comparison of experimental and numerical investigation. Issue 14 (October 2022) - Duan, Qingsong; Ma, Cunming; Li, Jiankun; Li, Qiusheng; Shang, Jingmiao
Open girder sections are vulnerable to vortex-induced vibrations (VIV) because of their bluff aerodynamic characteristics. A comparative investigation was conducted by wind tunnel tests and numerical simulation. Firstly, based on sectional model wind tunnel tests, the VIV performance of semi-open girder and separated edge-boxes open girder was studied with consideration of the influence of the equivalent mass, wind attack angle and damping ratio. The aerodynamic parameters Scruton number ( S c ) and Strouhal number ( S t ) of two girders were analyzed contrastively. In addition, VIV amplitudes corresponding to the real bridge girders were calculated by the linear and nonlinear theories. Then, flow fields around two semi-open girder sections were investigated on the basis of computational fluid dynamics. The results show that vertical and torsional VIVs of two open girders are observed, at +3°and +5° wind attack angles. There were two vertical VIV regions and the maximum amplitude in the second vertical VIV region is significantly larger than that in the first one. For the semi-open girder and separated edged-box open girder, the vertical VIV amplitudes at +5° wind attack angle is 115% and 75% larger than at +3° wind attack angle, respectively. The damping ratio could obviously mitigate the VIV of two girders and VIV amplitudes are decreased linearly with the S C number increases. There are vortexes above the girder deck at the opening position of the semi-open girder and the separated edge-boxes open girder. The oblique web and wind faring may break the large vortex into several smaller vortexes at the opening position, thus optimizing the vortex vibration performance of the girder. A thicker shear layer is formed at separated open-girder during the development of airflow towards backward of bridge deck, due to the effect of railings and the blunt boxes on the lower surface.